Un fenomeno pericoloso - Selvini, Attilio (GEOmedia, 2025)
Modern photogrammetry using drones—or rather RPAS—isn't something just anyone can do. These new techniques still require solid knowledge of topography and traditional aerial photogrammetry, along with strong skills in using computers and software. With much of the processing now automated, critical decisions—like setting flight parameters, acquiring ground control points, and choosing between vector or orthoprojection methods— directly impact the final outcome.